Readings in human development : concepts, measures, and policies for a development paradigm - Fukuda-Parr, Sakiko, 1950-; Shiva Kumar, A. K. (New Delhi ; New York : Oxford University Press, 2003)
Contributed articles on debates regarding how to evaluate economic development and quality of life of people with new social indicators.
"With a foreword by Amartya Sen."
Includes bibliographical references.
Shakib
Keywords: Economic development -- Social aspects -- Methodology; Human capital -- Methodology; Quality of life -- Methodology; Social accounting -- Methodology